Developing an Online Learning Module to Aid in Student Learning and Results - Mutiarani Zahra, Rastya; Sumiyadi, Sumiyadi; Cahyani, Isah; Sastromiharjo, Andoyo; Nuphanudin, Nuphanudin (Universitas Ahmad Dahlan, 2023)
Self-regulated e-learning modules are an innovative teaching method to increase student success and results in light of the desire to include technology in nursing education and the rising demand for online training. According to a learning requirements analysis, the addition of a self-directed, self-paced e-learning module might give students a way to more adequately get ready for a scenario simulating pediatric dehydration with medium realism. Three members of the faculty—a faculty topic specialist, a faculty content consultant, and a librarian/instructional designer—were assembled into a collaborative, interdisciplinary project team. Using the notion of self-regulated learning, the team created an online learning module. The purpose of this module is to better prepare undergraduate nursing students for pediatric simulation. It is an asynchronous, standalone, self-paced supplement. The inclusion of an online learning module will improve student engagement with the subject matter and encourage greater self-directed learning.